Neuronal Cx3cr1 Deficiency Protects against Amyloid β-Induced Neurotoxicity - Dworzak, Jenny (PLoS One, 2015)
Cx3cr1, the receptor for the chemokine Cx3cl1 (fractalkine), has been implicated in the progression and severity of Alzheimer’s disease-like pathology in mice, but the underlying mechanisms remain unclear. A complicating factor is that Cx3cr1 has been demonstrated in both neurons and microglia. Here, we have dissected the differences between neuronal and microglial Cx3cr1, specifically by comparing direct amyloid-β-induced toxicity in cultured, mature, microglia-depleted hippocampal neurons from wild-type and Cx3cr1(-/-) mice. Wild-type neurons expressed both Cx3cl1 and Cx3cr1 and released Cx3cl1 in response to amyloid-β. Knockout of neuronal Cx3cr1 abated amyloid-β-induced lactate dehydrogenase release. Furthermore, amyloid-β differentially induced depression of pre- and postsynaptic components of miniature excitatory postsynaptic currents, in a peptide conformation-dependent manner. Knockout of neuronal Cx3cr1 abated effects of both amyloid-β conformational states, which were differentiable by aggregation kinetics and peptide morphology. We obtained similar results after both acute and chronic treatment of cultured neurons with the Cx3cr1 antagonist F1. Thus, neuronal Cx3cr1 may impact Alzheimer’s disease-like pathology by modulating conformational state-dependent amyloid-β-induced synaptotoxicity.